Sigma factor RpoS positively affects the spoilage activity of Shewanella baltica and negatively regulates its adhesion effect - Zhang, Caili; Chen, Jiaqi; Pan, Xiaoming; Liu, Haimei; Liu, Yanlong (Frontiers in Microbiology, 2022)
Shewanella baltica is the dominant bacterium that causes spoilage of seafood. RpoS is an alternative sigma factor regulating stress adaptation in many bacteria. However, the detailed regulatory mechanism of RpoS in S. baltica remains unclear. This study aims to investigate the regulatory function of RpoS on spoilage activity and adhesion ability in S. baltica. Results revealed that RpoS had no effect on the growth of S. baltica, but positively regulated the spoilage potential of S.baltica accompanied by a slower decline of total volatile basic nitrogen, lightness and the sensory score of fish fillets inoculated with rpoS mutant. RpoS negatively regulated the adhesion ability, which was manifested in that the bacterial number of rpoS mutant adhered to stainless steel coupon was higher than that of the S. baltica in the early stage, and the biofilm formed on glass slide by rpoS mutant was thicker and tighter compared with S. baltica. Transcriptomic analysis showed that a total of 397 differentially expressed genes were regulated by RpoS. These genes were mainly enrichment in flagellar assembly, fatty acid metabolism/degradation and RNA degradation pathways, which were associated with motility, biofilm formation and cold adaptation. This study demonstrated that RpoS is a primary regulator involved in flagellar assembly mediated biofilm formation and cold adaptation-related spoilage activity of S. baltica. Our research will provide significant insights into the control of microbiological spoilage in seafood.